The labour market triangle. Employment protection, unemployment compensation and activation in Europe (Cheltenham, 2009)
"Currently, European governments are being challenged to find an optimal social policy strategy that fosters 'flexicurity’, whereby a flexible, well-functioning labour market is achieved, whilst protection for workers is maintained. This fascinating book presents an in-depth study of the particular combination of unemployment insurance, employment protection and active labour market policies prevalent in seven European countries. The editors explore the formal laws and regulations, as well as the administration and implementation of social policy, paying special attention to the role of the social partners. The country comparison shows that the combination of social policy instruments is important to labour market performance, but that multiple optimal mixes already seem to exist."